2019 IEEE VTS Asia Pacific Wireless Communications Symposium (APWCS) 2019
DOI: 10.1109/vts-apwcs.2019.8851632
|View full text |Cite
|
Sign up to set email alerts
|

Power-Imbalanced Low-Density Signatures (LDS) From Eisenstein Numbers

Abstract: As a special case of sparse code multiple access (SCMA), low-density signatures based code-division multiple access (LDS-CDMA) was widely believed to have worse error rate performance compared to SCMA. With the aid of Eisenstein numbers, we present a novel class of LDS which can achieve error rate performances comparable to that of SCMA in Rayleigh fading channels and better performances in Gaussian channels. This is achieved by designing power-imbalanced LDS such that variation of user powers can be seen both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In this section, we assess the performance of our proposed LDS code sets against the LDS sets in [12], for quadrature amplitude modulation (QAM) signaling. We observed that when the non-zero positions of the LDS code sets generated according to [12] are different than those of the proposed LDS code sets, the bit error rate (BER) performance of the former deteriorates substantially.…”
Section: Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we assess the performance of our proposed LDS code sets against the LDS sets in [12], for quadrature amplitude modulation (QAM) signaling. We observed that when the non-zero positions of the LDS code sets generated according to [12] are different than those of the proposed LDS code sets, the bit error rate (BER) performance of the former deteriorates substantially.…”
Section: Designsmentioning
confidence: 99%
“…In this section, we assess the performance of our proposed LDS code sets against the LDS sets in [12], for quadrature amplitude modulation (QAM) signaling. We observed that when the non-zero positions of the LDS code sets generated according to [12] are different than those of the proposed LDS code sets, the bit error rate (BER) performance of the former deteriorates substantially. Therefore, while generating the LDS codes of sizes 7 × 9 and 13 × 15 based on [12], the non-zero entries are kept in the same positions as those in the proposed LDS sets; however, the values of the non-zero entries are obtained by following the exact procedure outlined in [12].…”
Section: Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel sparse code multiple access (SCMA) scheme named delayed bit-interleaved coded SCMA(DBIC-SCMA) was investigated in [25] and significant improvements in error rate performance was achieved over the classical BIC-SCMA scheme. [26] indicated that the performance of LDS with the aid of Eisenstein number is comparable to that of SCMA in Rayleigh fading channels and better in Gaussian channels than that of SCMA.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, building upon our preliminary results in [16], we develop a novel class of powerimbalanced SCMA codebooks having power variation among different users for downlink transmission. By leveraging the power-imbalance (a unique trait of power-domain NOMA), we aim to take advantage of the "near-far effect" among different users in order to attain enhanced MPA decoding.…”
Section: Introductionmentioning
confidence: 99%